Análise do potencial para criação de geoparques em Roraima : estudo de caso na região da Serra do Tucano - Município de Bonfim - RR - Reis, Rhaina Peris (2018)
Geological heritage is an important protagonist in terms of protection of the geological, geomorphological and paleontological environment of the Earth. For this reason the first geoparks were created in Europe and more late for the world. In view of this need, the present study has the purpose of analysing the region of Serra do Tucano formation belonging to the municipality of Bonfim – RR as a potential area for geopark based on its geology, geomorphology and paleontology. The types of research used were bibliographic and descriptive. Descriptive research was carried out by the method of data collection and field observation in order to analyze qualitatively and quantitatively the potential geossítios classifying them according to their level of relevance. The said research was carried out with based on the methodology of Brilha (2016) and according to the data found were called four potential geological site: Pegada dos Dinossauros, Morro do Urubu, Morro da Antena and Praia das Sementes. Potential Geological site entitled Pegada dos Dinossauros and Morro Urubu presented International Scientific Relevance and Potential for Educational Use with National Relevance and Tourist Use of Local Relevance and low Risk of Degradation. The geological site in the potential Morro da Antena, presents itself with the best structure obtaining Scientific Value of International Level, Potential of Educational Use with National and Tourist Relevance with Local Relevance displaying low Risk of Degradation. The potential geological site beach of seeds obtains Scientific Value of National Relevance and Potential for Educational Use and Tourism of Local Relevance presenting a medium Risk of Degradation. From the findings found a field opened to Research in the area of Serra do Tucano formation dating from the cretaceous inferior period as well as the occurrence of siltitos and sandstones in the geomorphological dates of the same period. Such clues point to the capability of the Serra do Tucano formation for a future geopark.